An Analysis of Dynamic Governance Capability in Innovation Development in Bintan Regency - Budiman, Shahril; Junriana, Junriana; Matridi, Raja Abumanshur (ARISTO, 2022)
At the government level, upon the issuance of regional government regulations in Indonesia, innovation has been an obligation and an indication of regional competitiveness. Innovation is also an acceleration of governance including creating good governance arrangements, implementing bureaucratic reform agendas with dynamic governance values. Bintan Regency, as the most innovative regency in the category of borderline areas in Indonesia, received an Innovative Government Award (IGA) appreciation for the 2020-2021 period. This must ensure that the regional innovation agenda will continue to be sustainable. One of the important aspects in dynamic governance is the capability aspect in which government institutions must think ahead, think again and think beyond and that is included in every policy-making process, civil servants resources and performance implementation of the public sector bureaucracy in an attempt to bring together common consensus. This article aims to describe how the Bintan Regency government carries out adaptive policies through a dynamic governance capability approach in building ecosystems, government innovations in a sustainable manner. The findings of the present study discovered that the government's efforts to ensure future innovation through collaboration with universities as facilitators as well as evaluating the development of regional innovation in Bintan Regency for the regional innovation index. In addition, in encouraging the development of government innovation, advocacy for regional innovation policies and digital and non-digital services has been carried out, including the regional innovation monitoring team. This page is in Malay Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Malay to EnglishPRO Never translate Malay Never translate journal.umpo.ac.id